Posterolateral Corner Reconstruction Alone Using a Fibular-Based Technique in a Patient with Persistent Unstable Revision Total Knee Arthroplasty - Joseph T. Cline; Eduard Alentorn-Geli; J. H. James Choi; Joseph J. Stuart; Terry Kruger; Claude T. Moorman III (Case Reports in Orthopedics)
Posterolateral rotatory instability is a relatively uncommon cause of unstable total knee arthroplasty (TKA). In most cases, surgical treatment requires revision TKA into a more constrained design or thicker polyethylene liner. We present a case of a patient with unstable TKA who remained unstable after increasing thickness of the polyethylene liner and undergoing more constrained TKA. After several revision surgeries, the patient was still unstable. Posterolateral corner reconstruction with a fibular-based technique using a tibialis anterior allograft was performed. At 1-year follow-up, the patient was stable and asymptomatic and with excellent function. A soft-tissue procedure only (fibular-based posterolateral corner reconstruction) can be effective at restoring posterolateral rotatory stability in a patient with persistent instability after revision TKA.